KETERAMPILAN MENULIS NARASI MELALUI TEKNIK REKA CERITA GAMBAR SISWA KELAS VIII SMP NEGERI 1 SEMENDO DARAT LAUT UNTUK MENYONGSONG REVOLUSI INDUSTRI 4.0 - Louzi Laura Wagentini (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Narrative writing skills through technical storytelling drawings of class VIIII students of SMP Negeri 1 Semendo Darat Laut Muara Enim Regency. This study aims to find out and describe narrative writing skills through the technique of storytelling images of class VIII students of SMP Negeri 1 Semendo Darat Laut. The population of this study were all eighth grade students of SMP Negeri 1 Semendo Darat Laut in Muara Enim Regency in the academic year 2016-2017 with 123 students with a sample of 28 students. The method used in this research is descriptive method. The technique of analyzing data collection is done through test techniques and interview techniques.Based on the results of the data analysis of the narrative writing skills test, it is known that by using the storytelling technique the students become easier to frame the essay and determine the contents of each paragraph, this is evident from 28 sample people, only 1 person who did not pass and get good and complete scores. The Minimum Completion Criteria (KKM) set by the school with an average student score of 76.10 (good enough). From the results of interviews with Indonesian language teachers, it is known that by using a storytelling technique students' motivation in learning also affects writing skills, especially writing narratives.